Association between drug‐specific indicators of prescribing quality and quality of drug treatment: a validation study. (6th July 2015) - Wallerstedt, Susanna M.; Belfrage, Björn; Fastbom, Johan
Abstract Purpose To evaluate the concurrent validity of three European sets of drug‐specific indicators of prescribing quality Methods In 200 hip fracture patients (≥65 years), consecutively recruited to a randomized controlled study in Sahlgrenska University Hospital in 2009, quality of drug treatment at study entry was assessed according to a gold standard as well as to three drug‐specific indicator sets (Swedish National Board of Health and Welfare, French consensus panel list, and German PRISCUS list). As gold standard, two specialist physicians independently assessed and then agreed on the quality for each patient, after initial screening with STOPP (Screening Tool of Older Persons' potentially inappropriate Prescriptions) and START (Screening Tool to Alert to Right Treatment). Results According to the Swedish, French, and German indicator sets, 82 (41%), 54 (27%), and 43 (22%) patients had potentially inappropriate drug treatment. A total of 141 (71%) patients had suboptimal drug treatment according to the gold standard. The sensitivity for the indicator sets was 0.51 (95% confidence interval: 0.43; 0.59), 0.33 (0.26; 0.41), and 0.29 (0.22; 0.37), respectively. The specificity was 0.83 (0.72; 0.91), 0.88 (0.77; 0.94), and 0.97 (0.88; 0.99). Suboptimal drug treatment was 2.0 (0.8; 5.3), 1.9 (0.7; 5.1), and 6.1 (1.3; 28.6) times as common in patients with potentially inappropriate drug treatment according to the indicator sets, after adjustments for age, sex, cognition, residence, multi‐dose drug dispensing, and number of drugs. Conclusions In this setting, the indicator sets had high specificity and low sensitivity. This needs to be considered upon use and interpretation. Copyright © 2015 The Authors Pharmacoepidemiology and Drug Safety Published by John Wiley & Sons, Ltd.